Currency of full-text medical journals: CCML and MEDIS vs. MEDLINE. - McKinin, E J (1991)
The authors ask whether full-text versions of medical journals are available for searching sooner than their biblographic counterparts. The journals in question are those found in the Comprehensive Core Medical Library (CCML) from BRS Information Technologies and in Mead Data Central's MEDIS Current Journal Files. All journals in these two files are full-text, and neither file contains any indexing features. Update schedules for the full-text version of the MEDLINE journals in each of these files were compared with the most recent issue available in the National Library of Medicine's (NLM) MEDLINE on five different dates. The data revealed substantial fluctuation in comparative currency for MEDIS/MEDLINE over the period of the test. On the date of the last snapshot, June 8, 1990, MEDLINE and MEDIS were offering the same currency for 43% of the journals, and MEDIS was providing first access to 29% of the titles. The CCML/MEDLINE comparison showed less variation. In the last snapshot MEDLINE and CCML were providing access to the same issue for 36% of the journals, and CCML was offering first access to 14%. Prior to publication, this paper was submitted to all three vendors for comment. Significant portions of their responses are quoted.